2007
DOI: 10.1007/s00299-006-0292-5
|View full text |Cite
|
Sign up to set email alerts
|

Pyramiding transgenic resistance in elite indica rice cultivars against the sheath blight and bacterial blight

Abstract: Elite indica rice cultivars were cotransformed with genes expressing a rice chitinase (chi11) and a thaumatin-like protein (tlp) conferring resistance to fungal pathogens and a serine-threonine kinase (Xa21) conferring bacterial blight resistance, through particle bombardment, with a view to pyramiding sheath blight and bacterial blight resistance. Molecular analyses of putative transgenic lines by polymerase chain reaction, Southern Blot hybridization, and Western Blotting revealed stable integration and expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 63 publications
4
39
0
Order By: Relevance
“…In this case, the data also indicate that this strong effect is only due to the combined action of the thaumatin-like and chitinase proteins, independently of the Xa21 gene (Maruthasalam et al 2007). Some excellent levels of protection were also shown for kernel smut (caused by Tilletia barclayana; Zhu et al 2007) by pyramiding (Table 4).…”
Section: Disease Protection Quantitative Effectsmentioning
confidence: 80%
“…In this case, the data also indicate that this strong effect is only due to the combined action of the thaumatin-like and chitinase proteins, independently of the Xa21 gene (Maruthasalam et al 2007). Some excellent levels of protection were also shown for kernel smut (caused by Tilletia barclayana; Zhu et al 2007) by pyramiding (Table 4).…”
Section: Disease Protection Quantitative Effectsmentioning
confidence: 80%
“…Hence, it is possible that increased resistance in rice to R. solani after application of OA may be related to the accumulation of phenolics and defense related proteins. In recent years, there has been success in control of sheath blight by overexpression of antifungal proteins in rice plants through genetic engineering (Lin et al 1995;Datta et al 1999;Datta et al 2001;Kalpana et al 2006;Maruthasalam et al 2007;Shah et al 2009). However, it is suggested that the constitutive expression of defense genes may likely impose a considerable drain on energy and metabolic resources, whereas inducible defenses would impose a significantly lower metabolic cost (Herms and Mattson 1992;Heil and Bostock 2002).…”
Section: Discussionmentioning
confidence: 99%
“…PB1 and ADT38 using a biolistic method. The co-transformants exhibited an enhanced resistance against R. solani (Maruthasalam et al 2007). Transgenic rice plants of local cultivars developed through Agrobacterium-mediated transformation expressing rice chitinase gene RC7 exhibit an enhanced resistance (up to 33.3 %) to R. solani under glasshouse conditions (Nandakumar et al 2007).…”
Section: Introductionmentioning
confidence: 99%